Study of Congenital Anomalies of the Kidneys and Urinary Tract in Neonates - Chougule, Akshaya; Purkayastha, Jayashree; Lewis, Leslie; Aiyappa, Gourav; Barche, Apurv (Journal of Nepal Paediatric Society, 2018)
Introduction: Congenital anomalies of the kidneys and urinary tract (CAKUT) comprise various structural malformations that result from defects in morphogenesis of the kidney and/or urinary tract. In most cases, CAKUT are associated with infant mortality and morbidity in older children and adults. Hence this study was undertaken to follow up antenatally diagnosed cases of CAKUT and see their outcome in the first six months of life. Material and Methods: An observational follow up study was conducted in the department of Paediatrics in a tertiary care hospital. All inborn neonates, whose antenatal anomaly scans showed the presence of CAKUT were included in the study. Abdominal ultrasound (USG) were done on day three of life for all these neonates and those whose day three USGs showed presence of CAKUT were followed up over a period of six months and outcome was assessed. Results: CAKUT was more common among males. Hydronephrosis was the most common CAKUT in antenatal scans. Anomalies of the renal collecting system formed 93.9% of all CAKUT detected on antenatal anomaly scan and 57.4% of these resolved by six months of age. Abnormalities of the renal collecting system together formed 93.9% of all antenatally diagnosed CAKUT and were more common than abnormalities of the renal parenchyma which formed 6.1%. Postnatal resolution on day three USG was seen in seven out of 22 (31.8%) cases of antenatally diagnosed mild hydronephrosis irrespective of their site. Out of the 28 antenatally diagnosed hydronephrosis, 11 (39.3%) resolved at some point during the follow up period of six months. Conclusions: Antenatally diagnosed CAKUT were more common among male foetuses. On day three scan, 29.2% of CAKUT showed resolution. Hydronephrosis remained the most common antenatally as well as postnatally detected CAKUT. Anomalies of renal collecting system were better detected by antenatal scans than anomalies of renal parenchyma